Pemanfaatan Lahan Aset Desa Non-Produktif Melalui Budidaya Tanaman Pohon Balsa : Studi Kasus: Desa Sindangwangi - Sutarmin Sutarmin; Siti Badiatul Umroh; Tria Putri Yani; Meri Aguk Setiani (Jurnal Pengabdian Masyarakat, 2025)
This community service program, conducted in Sindangwangi Village, Brebes Regency, aims to optimize the use of unproductive village land to improve local welfare. A team from the University of Civilization initiated an empowerment project through the introduction of balsa tree (Ochroma pyramidale) cultivation as an alternative source of economic value. The program was implemented in several stages, including problem identification, land mapping, provision of agricultural equipment, training, and technical mentoring for the community. The villagers received practical guidance on nursery preparation, planting techniques, and tree maintenance. As a result, six hectares of idle land that had been overgrown with weeds were successfully cleared, and 1,000 balsa seedlings were planted as demonstration plots. In addition to improving land productivity, this activity significantly enhanced community knowledge and skills in sustainable forestry management. The harvested balsa is expected to generate approximately IDR 100 million in village income within five years. This success demonstrates that collaboration between higher education institutions and local governments can effectively transform non-productive assets into profitable and environmentally friendly economic resources, supporting sustainable rural development and the achievement of the SDGs at the village level.